Early Studies on Protoplast Isolation of Ludisia discolor, A Wild Orchid - Ranjetta Poobathy; Rahmad Zakaria; Syed Mohd. Edzham Syed Hamzah; Sreeramanan Subramaniam (Tropical Life Sciences Research, 2016)
The terrestrial Ludisia discolor, also referred to as the jewel orchid is prized for the quality of its leaves. L. discolor is known as a medicinal herb and is touted for its heat- and pathogen-resisting qualities. L. discolor is valuable in the production of both flavonoids and anthocyanins, antioxidants that are exalted in the health industry. Plant cell cultures have emerged as alternative sources of anthocyanin production. Plant protoplast cultures are used frequently in transient gene expression studies and in the establishment of callus and cell suspension cultures. Benefits of plant protoplast system include similarity to cells found in plant tissues, reproduction under controlled conditions, and prevention of masking of stress responses to previous handling techniques. A study was conducted to assess the amenability of the stem and leaves of L. discolor to protoplast isolation. The stem and leaf segments were weighed, sliced into thin layers, immersed in a digestion medium, washed and then cultured onto a recovery medium. Results indicated that the production of plant protoplasts from L. discolor may be viewed as an alternative in the generation of cell cultures and ultimately in the production of anthocyanins from the cell cultures.